A clearer picture: Towards a new framework for the study of cultural transduction in audiovisual market trades - Uribe-Jongbloed,Enrique (2014)
This paper presents a theoretical and methodological revision which clarifies and organizes the concepts on the trade of audiovisual products between different cultural markets. It explores the concept of cultural proximity (Straubhaar, 1991) and the latest discussions on cultural translation (Conway, 2012) and cultural universals and lacunae (Rohn, 2010, 2011). After analyzing the various academic perspectives, the paper proposes a new framework, which defines more clearly the terminology, thus making a tool for comparative studies of audiovisual trade. This framework is divided into four aspects: market, product, people and process. Previous concepts are narrowed down and new concepts are developed to fill in the conceptual gaps.